Twinkling Artifact on Intracerebral Color Doppler Sonography - Khan, Haleem G.; Gailloud, Philippe; Martin, Jean-Baptiste; Khaw, Nathalie; Spadola, Luca; Rüfenacht, Daniel A.; Terrier, François (American Journal of Neuroradiology, 1999)
Summary: Transcranial Doppler sonography shows potential as a noninvasive technique for long-term follow-up of treated intracranial saccular aneurysms. This technical note describes a color Doppler artifact related to microcoil architecture that might represent a potential pitfall in transcranial Doppler sonographic evaluation of aneurysmal cavity thrombosis, since it may be wrongly interpreted as residual flow or aneurysmal cavity recanalization.